Predictive Factors for Postoperative Outcome in Children with Jejunoileal Atresia - Jarkman, Charlotta; Salö, Martin (The Surgery Journal, 2019)
Background Jejunoileal atresia is a relatively rare congenital gastrointestinal requiring surgery and long postoperative care. The postoperative outcome is affected by many factors and this study focuses on finding predictors for time to full enteral feeding, length of hospital stay (LOH), and postoperative complications.Methods This was a retrospective study of all children operated for isolated jejunoileal atresia between 2001 and 2017 at a tertiary center of pediatric surgery. Independent variables regarding demographical-, operative-, and postoperative data were abstracted. Primary outcome was time to full enteral feeding, LOH, and postoperative complications in terms of reoperation or central line complication. Any significant variables from the univariate analysis were further analyzed with logistic regression and presented as odds ratio with 95% confidence interval.Results After exclusion because of concomitant gastroschisis (n = 1), and death before discharge (n = 2), 47 patients were further analyzed (49% boys, 53% premature). No significant differences could be seen in the univariate analysis between children with short and long time (median > 17 days) to full enteral nutrition. Patients with longer LOH (median >32 days) had significantly lower birth weight compared with those with shorter LOH; median 2,550 g versus 2,980 g (p = 0.04). Patients with a central line complication had significantly longer median time to full enteral feeding (median 27 vs. 12 days, p = 0.03), and significantly longer median LOH (median 43 vs. 21 days, p = 0.03), but these parameters were not significant in a multivariate analysis. No significant results were found regarding reoperation.Conclusion Low birth weight seems associated with an increased LOH in children operated on for jejunoileal atresia, and central line complications seem related to the duration with central line in this group. The small cohort may constitute a power problem in this study and further research regarding the included variables may reveal more potential predictors for the postoperative outcome.
Keywords: jejunoileal atresia; outcome; complication